Sudden upsurge of COVID-19 cases in China: A global threat - Yogesh, Sai; Singh, Tanya; Kashyap, Abhishek; Banerjee, Indrajit (Journal of Advances in Internal Medicine, 2023)
The ongoing COVID-19 pandemic has led to an unprecedented global health crisis with a significant impact on people's daily lives. Despite dealing with the pandemic for over three years, the situation still remains uncertain, with the emergence of new variants posing a threat to the population's health. China's dynamic zero-COVID policy was initiated in August 2021, to control the rapid spread of the novel virus, which proved successful. However, the policy's draconian approach and severe economic ramifications led to widespread protests and civil unrest, ultimately compelling the Chinese government to lift imposed restrictions. The emergence of the new Omicron variant, which has shown high transmissibility and a decrease in vaccine efficacy, has posed a new challenge in the fight against COVID-19. The abandonment of the zero-COVID policy has resulted in an increase in COVID-19 cases in China, with lack of natural hybrid immunity being one of the primary contributing factors. The situation requires close monitoring, and effective measures should be implemented to control the spread of the virus and mitigate its impact on people's lives.